Establishment of age-specific reference intervals for AMH in Indian women and enhancing its use as a diagnostic marker in PCOS - Sengupta, Sohini; Rawat, Sneha; Upadhay, Sonu; Chaudhary, Krishnagopal; Singh, Bipendra; Halim, M.; Gupta, Paritosh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Anti Mullerian hormone (AMH) level is a reliable marker of ovarian reserve. It is known to be influenced by factors like age, ethnicity, and ovarian pathology. Establishment of age-specific reference intervals for AMH, characteristic of different nationalities, is therefore of utmost importance. Serum AMH is known to be elevated in women with polycystic ovarian syndrome (PCOS). It is desirable to determine a population-specific cut-off of AMH, for it to be used as a diagnostic marker for PCOS. Methods: Serum AMH, luteinizing hormone (LH), follicle-stimulating hormone (FSH), Estradiol, Progesterone and Testosterone assays were analyzed in 1978 Indian women, in the age range of 12–50 years. Age-specific reference intervals for AMH were derived for the study population. The cohort of study subjects were then divided into two groups, based on AMH values and clinical history: Control group, and patients with PCOS. The cut-off value of AMH in the study population, corresponding to the diagnosis of PCOS, was also established. Results: Upper 95th percentile limits of reference intervals for the 18-25 26–30, 31–35, and 36–40, 41-45 and >45 age groups were 9.69, 7.60, 6.50, 6.1, 4.80 and 4.5 ng/ml respectively. In the PCOS group the 5th percentile value was 7.80 ng/ml and the upper 95th percentile was 21.81 ng/ml. The median percentile in PCOS group was 10.40 ng/ml. ROC analysis was done to obtain optimal cutoff values for each age group with better discriminative power than the reference limits. The best cut-off point of AMH value for PCOS in our study population was 7.51ng/ml. The sensitivity and specificity were 99.4% and 95.5%, respectively. The calculated area under the Receiver operating characteristic (ROC) curve was 0.988 (95% CI: 0.984-0.991, P <0.001). AMH, LH, and LH/FSH ratio was significantly higher in the PCOS group than in the control group (p < 0.001 for all comparisons). LH/FSH ratio was more than 2 in the PCOS group compared to controls. Serum Testosterone was significantly higher in PCOS. Conclusions: The study aids to establish a biological reference interval for AMH, specific for different age groups in Indian women. 7.51ng/ml has been derived as a diagnostic cut-off of AMH for PCOS in our study population. The establishment of age-specific reference intervals, and syndrome-specific cut-offs in the Indian population will help overcome the influence of variables and broaden the use of AMH in women’s health.